Heat Transfer During Polymer Selective Laser Sintering Process: Parametric Analysis - Siginer, D (American Society of Mechanical Engineers, 2022)
The laser transmission in the polymer powder bed includes three parts during the selective laser sintering (SLS) process: absorption, reflection, and scattering. Because of the granular nature of the polymer powder, the scattering phenomena causes the photons isotropic travel in the medium, which affects directly the photons’ distribution in the powder bed. In this paper, we numerically simulate the laser heat source traveling in a powder polymer bed, as in the SLS process, by introducing the Mie theory with Monte-Carlo method, instead of the Bear-Lambert Law, to correctly represent the heating energy distribution in the material. The obtained energy distribution is then introduced in the energy equation to solve the heat transfer problem in such non homogeneous medium. All the material transformation are also introduced, as the melting process, the coalescence, air diffusion and porosity evolution, based on classical theories. Meanwhile, we carry out a parametric thermal analysis and discussed based on process parameters, like the laser power, laser moving length and the material preheating temperature. Their influence on the temperature evolution is quantified. These analysis results can be used as a guide for providing technical database to SLS process, helpful for various industries in automotive, aerospace and medical areas. Copyright © 2022 by ASME.